2004
DOI: 10.1002/eej.10318
|View full text |Cite
|
Sign up to set email alerts
|

A study of collaborative operation between a new energy type dispersed power supply system and SMES by modified Euler type moving average prediction model

Abstract: SUMMARYIn this paper, the modified Euler type Moving Average Prediction (EMAP) model is proposed in order to operate a dispersed power supply system using new energy in autonomous mode. Furthermore, the EMAP model is used to operate a new type of dispersed power supply system consisting of a large-scale photovoltaic system (PV), a fuel cell (FC), and a small-scale superconducting magnetic energy storage system (SMES). This distributed power supply system can meet the multiple-quality electric power requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…2(a), investigating required EDLC capacity [4][5][6]. In order to compare simulation results for these models, simulations were performed for N/M-point MA model, M-division N-point EMAP model with M and N parameters of 8 and 1920, respectively, as well as AC-EMAP model with variable parameters.…”
Section: Simulation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…2(a), investigating required EDLC capacity [4][5][6]. In order to compare simulation results for these models, simulations were performed for N/M-point MA model, M-division N-point EMAP model with M and N parameters of 8 and 1920, respectively, as well as AC-EMAP model with variable parameters.…”
Section: Simulation Studymentioning
confidence: 99%
“…Considering that prediction procedure of smoothed component of fluctuating load is effective for capacity reduction of the energy storage for new energy type dispersed power supply, the authors previously proposed a modified Euler type Moving Average Prediction (EMAP) model, as one of the above-mentioned collaborative methods, which was applied to a new energy type dispersed power supply to be operated in autonomous mode, consisting of fuel cells (FC), photovoltaic array (PV) as well as electric double layer capacitor (EDLC) with rapid charging and discharging characteristics [4][5][6]. It was reported that this system as well as the collaborative operation method are feasible, and that the EMAP model is effective for reduction of EDLC capacity compared to the usual moving average (MA) model.…”
Section: Introductionmentioning
confidence: 99%
“…However, the data processed by the MA method shows a certain time delay (group delay time) as compared to the original time series signals, and the required capacity of EDLC becomes large. In order to avoid this drawback, the authors already proposed EMAP model, the details of which were fully explained already in reference [7].…”
Section: A M Division N Points Emap Modelmentioning
confidence: 99%
“…Applying Euler method to the MA model, the sum of data processed by the MA method and its derivative multiplied by the delay time can express approximately the real MA processed data after the delay time. This is the basic concept of the modified Euler type Moving Average Prediction (EMAP) model proposed by the authors in reference [7].…”
Section: A M Division N Points Emap Modelmentioning
confidence: 99%
See 1 more Smart Citation